Les processus d'intégration régionale, vecteurs de recomposition du système international ? - Petiteville, Franck (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1997)
Since the late eighties, the new regionalism is the most important wave of regionalism ever experienced in the world: every continent is now involved in one or several regional integration processes. This article aims at assessing the real impact of these processes on the international System. The method consists of comparing and building typologies of the main regional integration processes which have been created out of Europe, according to four criteria: the sense of the integration, the quality of political cooperation between the member states, the degree of economic integration, and the degree of institutional and political integration. The outcome of the analysis is that, except from Europe, integration is rarely scheduled to go deep or has a real chance to go deep in the short term. Hence the ability of the new regionalism to shape the international system deeply remains quite limited.